Improving Police Use of Force: A Policy Essay on National Data Collection. (March 2018) - Shane, Jon M.
Documenting police use of force has been an issue in the United States since at least 1931. As of July 2016, there is still no standardized national data collection effort, despite a call from several presidential and civil rights commissions to do so. Without accurate and timely national data, a moral panic of sorts unfolds that replaces rational thought and debate necessary to enact public policy. Moreover, without such data, it is virtually impossible to estimate the incidence and prevalence of police use of force, which leaves U.S. law enforcement agencies at a tremendous disadvantage for improving practices. This essay briefly examines the history of calls to improve police practices through collecting national use of force data and then offers a practical solution based on rational-technical theory of organizations with a brief analysis of a new promising, but limited, data set. The essay concludes with a proposed research agenda should national data become available through pending legislation H.R. 306, National Statistics on Deadly Force Transparency Act of 2015.